Model dan Metode Pembelajaran Berbasis STEAM pada Mata Pelajaran Biologi SMA - Dewi Ratna; Rita Retnowati; Surti Kurniasih (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
A teacher's understanding of learning will be seen from how the teacher applies it in teaching and learning activities. A teacher must know the strategy in teaching. This is related to learning models, techniques, and learning methods. In addition, the teacher must also be able to create a conducive, safe, comfortable, and enjoyable learning atmosphere. So it is important for a teacher to explore related models, learning methods with new innovations. One of them is by integrating STEAM learning into these learning models and methods. So far, not much research has been done on STEAM-based learning models and methods in biology subjects. The purpose of this study was to analyze which learning models and methods are often used, as well as which materials are most often used to apply STEAM-based learning to high school biology material. This research is a qualitative descriptive study by distributing questionnaires via Google forms which are distributed via WhatsApp groups to high school biology teachers in Bogor Regency, with 48 people as respondents. The instrument is a questionnaire on the Google form which consists of 15 questions, which contain questions about the media that is often used in class, what models and methods are often used in biology subjects, as well as the teacher's knowledge of STEM, and in any material in biology subjects the teacher applies STEAM learning. The results showed that the most widely used learning model was the Problem Based Learning (PBM) model (43.8%), followed by Project Based Learning (PjBL) (20.8%). Teachers who use the discussion method 16.7%, the cooperative method 12.5%, and 6.3% use the lecture method. For knowledge about STEAM, the results show that 91.7% of respondents know about STEAM, and 68.8% of respondents have implemented STEAM-based learning. For the application of STEAM, most of it was done on material change and environmental preservation as much as 22.9%. The data obtained were analyzed qualitatively, then displayed in the form of pie charts and bar charts.